2022
DOI: 10.1126/sciadv.abm2510
|View full text |Cite
|
Sign up to set email alerts
|

A systems biology approach identifies candidate drugs to reduce mortality in severely ill patients with COVID-19

Abstract: Despite the availability of highly efficacious vaccines, coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lacks effective drug treatment, which results in a high rate of mortality. To address this therapeutic shortcoming, we applied a systems biology approach to the study of patients hospitalized with severe COVID. We show that, at the time of hospital admission, patients who were equivalent on the clinical ordinal scale displayed significant differenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 131 publications
1
16
0
Order By: Relevance
“…A recent study based on single cell omics data confirmed that T cell populations rather than B cell populations are significantly reduced in critically ill COVID‐19 patients. 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
“…A recent study based on single cell omics data confirmed that T cell populations rather than B cell populations are significantly reduced in critically ill COVID‐19 patients. 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
“…Values were expressed as medians. N sample = MOD (10) and SEV (16) for each endpoint (A or B), CTRL (6). Yellow asterisks = Infected A versus controls A; Red asterisks = Infected B versus Infected A; Blue asterisks = Infected B versus controls A. E and F : Bar charts depicting intracellular protein levels of CCL3 (Panel E) and IL-1B (Panel F).…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetic changes in host cells during COVID-19 have already been described and are associated with the regulation of the SARS-CoV-2 cycle ( 25, 26 ), the disease severity ( 17, 26 ) or the prognosis for critically ill patients ( 16, 26 ). However, to the best of our knowledge, this is the first work to demonstrate that pharmacological modulation of the leukocyte epigenetic marks favorably regulates central components of hyperinflammation in moderate and severe forms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Here we proposed examples by adapting designs applied to study the host response to infections, detect somatic mutations in cancers and evaluate embryonic development. 20 , 21 , 22 , 23 …”
Section: How To Test the Hypothesismentioning
confidence: 99%